Technology and Tradition: Spatio-temporal mapping of Temple Architecture in South and Southeast Asia - Datta, Sambit (2015)
Mapping the fragmented and heavily eroded remains of early temple architecture across space and time poses several challenges. This paper describes an ongoing research project that addresses these challenges through the analysis and reconstruction of shape and form from digital datasets. The project re-assembles ambiguous and fragmentary evidence from temple sites in India, Java and Cambodia to provide a robust and empirical understanding of the lineage and connections between the temple building traditions of South and Southeast Asia. The significance of the project lies in its emphasis on the application of modern technological tools that quantify the results, the degree of accuracy and ambiguity in the reconstruction across the acquisition, processing and reconstruction phases. To quantify the process of establishing formal continuity, the method combines image-based analysis methods with flexible graphical simulation techniques for geometric reconstruction. A key aspect of the method is the maintenance of multiple “ground truths” from plural sources of partial evidence. The paper summarizes some early results in the geometric modeling of early temples and concludes with an overview of how technology can assist in the spatio-temporal mapping of traditional architecture in South and Southeast Asia. Keywords: Digital data acquisition, flexible modeling, heritage reconstruction and visualization, traditional architecture, geometry processing and algorithms